2012
DOI: 10.1111/j.1365-2672.2012.05388.x
|View full text |Cite
|
Sign up to set email alerts
|

Cocultivation of phytopathogenic Fusarium and Alternaria strains affects fungal growth and mycotoxin production

Abstract: Aims A laboratory study was conducted to evaluate the influence of cocultivation of toxigenic Fusarium (F.) and Alternaria (A.) fungi with respect to growth and mycotoxin production. Methods and Results Fusarium culmorum Fc13, Fusarium graminearum Fg23 and two Alternaria tenuissima isolates (At18 and At220) were simultaneously or consecutively co‐incubated on wheat kernels in an in vitro test system. Fungal biomass was quantified by determining ergosterol content. Three Fusarium toxins (DON, NIV and ZON) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 50 publications
3
35
0
1
Order By: Relevance
“…A recent study reported the suppression of toxin production (by more than 95%) in Alternaria tenuissima when the fungus was co-cultivated with F. culmorum or F. graminearum [27]. We thus plotted alternariol against trichothecene concentrations, but could not detect any correlation.…”
Section: Resultsmentioning
confidence: 95%
“…A recent study reported the suppression of toxin production (by more than 95%) in Alternaria tenuissima when the fungus was co-cultivated with F. culmorum or F. graminearum [27]. We thus plotted alternariol against trichothecene concentrations, but could not detect any correlation.…”
Section: Resultsmentioning
confidence: 95%
“…Interactions of fungi and bacteria with Alternaria could exist more often in competition and in antagonistic processes than in undisturbed coexistence. Few studies dealing with the co-occurrence of Fusarium and fluorescent pseudomonads with Alternaria suggest the implication of mycotoxins as antagonistic substances in these interactions [52,53] Simultaneously, competition processes between different fungal genera affect the production of mycotoxins or increase the metabolization of toxins [54,55]. That means that the production of mycotoxins in natural habitats is influenced by biotic and abiotic factors and could represent various toxin profiles and different concentrations of mycotoxins [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…(Jones et al, 1997) or other toxigenic fungi such as Alternaria spp. (Müller et al, 2012); (2) in temperate areas, DON is the most prevalent mycotoxin in wheat (Mishra et al, 2013).…”
Section: Discussionmentioning
confidence: 99%